Disordered eating and compulsive exercise in collegiate athletes: Applications for sport and research - Power, K.; Kovacs, S.; Butcher-Poffley, L.; Wu, J.; Sarwer, D. (The Sport Journal, 2020)
Over the last three decades, a large body of research has examined the issue of eating disorders, both formal diagnoses and subclinical features, as well as compensatory behaviors in National Collegiate Athletic Association (NCAA) athletes. In general, this literature suggests that large numbers of student-athletes engage in disordered eating and compensatory behaviors; smaller percentages have symptoms that reach the threshold of formal diagnoses. Increased symptoms are associated with reduced athletic and academic performance, both of which may impact psychosocial functioning later in adulthood. Unfortunately, a number of methodological shortcomings across this body of research (e.g., studies with insufficient sample sizes, inappropriate comparison groups, and suboptimal or biased psychometric measures) limit the confidence that can be placed in these findings, underscoring the need for a new generation of studies. This paper provides an overview of this literature, focusing on issues of gender differences, sport type, and age. It also highlights the relationship between disordered eating and compulsive exercise, a compensatory behavior that is highly prevalent among collegiate athletes. The health and athletic performance consequences of eating disorders in conjunction with compulsive exercise are also discussed. In addition, a focus on more recently recognized eating disorders, such as binge eating disorder and the night eating syndrome is underscored. Future work in this area needs to include the most methodologically rigorous measures available in order to aid most appropriately coaches and athletic trainers in promptly identifying at-risk athletes and to inform future prevention and treatment efforts.